Notice of a Silver Brooch with Black Letter Inscription and Ornamentation in Niello, the Property of Miss Steven of Bellahouston, and of a Large Brass Highland Brooch with Incised Ornamentation, the Property of Mrs W R Mitford, 33 Coates Gardens Edinburgh - Brook, Alexander J S (Proceedings of the Society of Antiquaries of Scotland, 1889)